THE INEDIBLE: VISUALS AND FOOD ANXIETY - Chakraborty, Dalia (PEOPLE: International Journal of Social Sciences, 2020)
Anxiety about food as a principal item of consumption is universal. Who can and can not eat what and when, are, in most cases, normatively settled. Any violation of such norm generates anxiety. Though the focus of this paper is on the visuals, it is needless to point out, seeing food or drink invariably acts in conjunction with smelling and hearing. We usually refer to the enticing power of visuals of edible. But images of food/drink also generate anxiety regarding inedible, leading sometimes to dietary changes like the decrease in consumption of red meat, street food or food from restaurants. This paper explores how the visuals often set up, sometimes by design, distraction, disenchantment and caution - thereby inhibiting consumption. The visuals that generate food anxiety in regard to routinized everyday consumption as well as to the consumption experience in extraordinary times have been probed. The site chosen is the city of Kolkata. The inquiry is confined to women because they are still in charge of supervising food and hence have a definite association with the circulation of food taboos. The work is confined to the upper-middle-class or rich sections of the city women because among the poor and food-insecure people, there is not much of a choice regarding consumption. The focus is on contemporary experience, without neglecting its historical dynamics.